Analysis on The Influence of Sollar Irradiation And Rotational Speed of Centrifugal Submersible Pumps Efficiency in Solar Water Pump Systems Technology - Shafa, Naura; Rhakasywi, Damora; Fahrudin, Fahrudin (PT Mattawang Mediatama Solution, 2023)
This study aims to analyze the effect of solar irradiation and rotational speed on the efficiency of centrifugal submersible pumps in solar water pump systems. The research was conducted using measuring instruments such as the PS2-4000 Controller on a PATS system with a capacity of 5940 Wp, Autodesk Inventor 2022, Microsoft excel, and Rstudio. The independent variables used were the level of solar irradiation and rotational speed obtained every day for two weeks from 07.00 – 17.00. The dependent variable is obtained from a literature study and the PATS system used. The PATS system uses a LORENTZ PS2-4000 C-SJ17-4 centrifugal submersible pump and a PLTS with a capacity of 5940 Wp with a static head design of 20 m. Data collection was carried out based on actual data taken at the installation location of the PATS system and the velocity triangle analysis approach based on pump geometry. Data collection at the location was carried out using the pump controller PS2-4000 and COMPASS software. Data processing is done using Excel and Rstudio software. The results of data processing will be presented in the form of a curve that explains the relationship between the two or three variables studied. Based on this curve, results and conclusions can be obtained regarding the effect of solar irradiation and rotational speed on the efficiency of centrifugal submersible pumps in solar water pump systems. Data processing is done using Excel and Rstudio software. The results of data processing will be presented in the form of a curve that explains the relationship between the two or three variables studied. Based on this curve, results and conclusions can be obtained regarding the effect of solar irradiation and rotational speed on the efficiency of submersible centrifugal pumps in solar water pump systems. Data processing is done using Excel and Rstudio software. The results of data processing will be presented in the form of a curve that explains the relationship between the two or three variables studied. Based on this curve, results and conclusions can be obtained regarding the effect of solar irradiation and rotational speed on the efficiency of submersible centrifugal pumps in solar water pump systems.